The role of Universiti Teknologi MARA (UiTM) in education and social mobility in Malaysia / Ahmad Naqiyuddin Bakar … [et al.] - Bakar, Ahmad Naqiyuddin; Shuib, Adibah; Mahmud, Mohammad Bastyian; Ridzuan, Mohd Rozaimy (Universiti Teknologi MARA, 2020)
The article examines the role of Universiti Teknologi MARA (UiTM) and its role in promoting social mobility through education. The role of higher education exhibits differences and influenced by social origin, job mobility and class inequalities. In‐depth interviews with six intergenerational graduates of UiTM and observations of general social mobility provide insights into the way in which UiTM graduates thrive themselves in the social landscape. Results illustrate that adaptation of UiTM graduates in the light of their social origin and earlier study in UiTM support the gross observation of a stronger chance of their betterment in the society. The potential to thrive by UiTM graduates appears to be related to their advanced education as well as their previous level of studies that contribute to the destiny and job mobility. Little direct evidence is found, however, to explain variations of adjusting to the society and job mobility by graduates whom are from middle to upper income families. A tentative suggestion is proposed that significant composition of graduates of UiTM has successfully reduced class inequalities among different races in Malaysia. It is recommended that future research should use different methods, such as experiments or detailed observations, to gain a better viewpoint on the impact of UiTM through its academic offerings.